Pendidikan Anak Dalam Keluarga Perspektif Tafsir al-Mishbah Karya M. Quraish Shihab: Studi Literasi Al-Qur’an Surat Luqman Ayat 13-19 - Zuhrotul Khofifah; Moch Mahsun (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2020)
The family is the first place for children's growth and development. Where children get influence from the family at a very important and most critical period in children's education, namely the first year of their life (pre-school age), the family plays an important role in the education of first-year children even forever. To get a quality generation in providing pure education from the qur'an. This research uses literature study, the main object is surat luqman ayat 13-19 in the tafsir of al-misbah. And supported by books and other literature theoretically that promote the justification of reason and scientific logic. The results of this study provide an important role for families, especially parents, in educating children (starting early age) both in terms of ethics and monotheism in educating children. It also encourages the creation of human resources that embed children's education in families in indonesia.